2014
DOI: 10.1177/1057567714535631
|View full text |Cite
|
Sign up to set email alerts
|

Threats and Violence in the Care Sector

Abstract: Workplace violence is a complex occupational hazard that health care staffs are facing in today’s work environment. This study examines the safety measures recommended by staff in occupational injury reports filed in the wake of violence- and threat-related injuries. The results suggest that measures relating to psychosocial factors and structural factors such as adequate staffing are much more important than surveillance, staff training, and penal sanctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Participants described being limited by industrial agreements and insufficient funding, which restricted the number of staff allocated to care for patients at risk of perpetrating violence. Insufficient staffing levels, whether in number or skill mix, are known to contribute to WPV (Farrell, Shafiei, & Chan, 2014;Wikman, 2014). The mix of staff rostered to work must encompass the knowledge and ability to provide safe care, as well as the interpersonal skills required to de-escalate situations, and reduce WPV (Martin & Daffern, 2006).…”
Section: Sufficient Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants described being limited by industrial agreements and insufficient funding, which restricted the number of staff allocated to care for patients at risk of perpetrating violence. Insufficient staffing levels, whether in number or skill mix, are known to contribute to WPV (Farrell, Shafiei, & Chan, 2014;Wikman, 2014). The mix of staff rostered to work must encompass the knowledge and ability to provide safe care, as well as the interpersonal skills required to de-escalate situations, and reduce WPV (Martin & Daffern, 2006).…”
Section: Sufficient Resourcesmentioning
confidence: 99%
“…Working alone increases the risk of WPV, and where the risk of violence is high, staff should not work alone (Morken, Johansen, & Alsaker, 2015;Wikman, 2014). Yet participants reported that risk assessment for home visiting services did not always reflect the true level of risk, putting staff in danger.…”
Section: Sufficient Resourcesmentioning
confidence: 99%